2006
DOI: 10.1038/nature04723
|View full text |Cite
|
Sign up to set email alerts
|

Loss of autophagy in the central nervous system causes neurodegeneration in mice

Abstract: Protein quality-control, especially the removal of proteins with aberrant structures, has an important role in maintaining the homeostasis of non-dividing neural cells. In addition to the ubiquitin-proteasome system, emerging evidence points to the importance of autophagy--the bulk protein degradation pathway involved in starvation-induced and constitutive protein turnover--in the protein quality-control process. However, little is known about the precise roles of autophagy in neurons. Here we report that loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

102
2,625
6
26

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,232 publications
(2,800 citation statements)
references
References 29 publications
102
2,625
6
26
Order By: Relevance
“…In fact, it has been shown that FOXO factors participate in the regulation of genes responsible for two main mechanisms of intracellular clearance: autophagy and the ubiquitin‐proteasome system (Webb & Brunet, 2014). Defects in autophagy, the process of degradation and recycling of cytoplasmic proteins and organelles in response to starvation have been associated with premature aging and age‐related disorders (Hara et al ., 2006; Komatsu et al ., 2006; Jung et al ., 2008; Pickford et al ., 2008; Masiero et al ., 2009; Lee et al ., 2010a, 2010b). FOXOs affect the expression of genes involved in autophagy and mitophagy (muscle‐specific autophagy) in muscle cells from flies (dFOXO) to mammals (FOXO3), allowing adaptation of the tissues to starvation (Zhao et al ., 2007; Sengupta et al ., 2009; Demontis & Perrimon, 2010).…”
Section: Foxo and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been shown that FOXO factors participate in the regulation of genes responsible for two main mechanisms of intracellular clearance: autophagy and the ubiquitin‐proteasome system (Webb & Brunet, 2014). Defects in autophagy, the process of degradation and recycling of cytoplasmic proteins and organelles in response to starvation have been associated with premature aging and age‐related disorders (Hara et al ., 2006; Komatsu et al ., 2006; Jung et al ., 2008; Pickford et al ., 2008; Masiero et al ., 2009; Lee et al ., 2010a, 2010b). FOXOs affect the expression of genes involved in autophagy and mitophagy (muscle‐specific autophagy) in muscle cells from flies (dFOXO) to mammals (FOXO3), allowing adaptation of the tissues to starvation (Zhao et al ., 2007; Sengupta et al ., 2009; Demontis & Perrimon, 2010).…”
Section: Foxo and Autophagymentioning
confidence: 99%
“…The mechanism(s) by which Foxo factors contribute to lifespan remain elusive. As previously mentioned, decreased autophagy has been related to premature aging and age‐related associated disorders (Hara et al ., 2006; Komatsu et al ., 2006; Jung et al ., 2008; Pickford et al ., 2008; Masiero et al ., 2009; Lee et al ., 2010a, 2010b). Foxo factors have been shown to regulate autophagy in mouse muscle, particularly Foxo3, which induces the expression of several autophagy genes and increases autophagosome formation (Mammucari et al ., 2007; Zhao et al ., 2007; Webb & Brunet, 2014).…”
Section: Animal Modelsmentioning
confidence: 99%
“…A growing number of reports have linked malfunctioning of autophagy with aging, highlighting the role of autophagy as an anti‐aging cellular mechanism (Chang, Kumsta, Hellman, Adams & Hansen, 2017; Cuervo, 2008; Garcia‐Prat et al., 2016; Madeo, Zimmermann, Maiuri & Kroemer, 2015; Rubinsztein, Marino & Kroemer, 2011). Furthermore, genetic inhibition of this degradative process recapitulates features associated with aging and age‐related diseases (Hara et al., 1997; Komatsu et al., 2006, 2007; Menzies et al., 2017). Loss of protein/organelle quality control is a universal hallmark of aging, and malfunctioning of autophagy with age contributes to this gradual accumulation of damaged proteins and dysfunctional organelles (Kaushik & Cuervo, 2015; Kennedy et al., 2014; Lopez‐Otin, Blasco, Partridge, Serrano & Kroemer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other essential autophagy‐related proteins such as Atg7 and Atg17 likewise demonstrate significant impacts toward neural homeostasis and AD progression. In particular, conditional deletion of Atg7 results in massive neuronal death, behavioral impairments, and accumulation of intracellular Aβ (Komatsu et al., 2006; Komatsu, Wang et al., 2007; Nilsson, Loganathan, Sekiguchi, Matsuba, & Hui, 2013), while Atg17 ‐null neuronal cells suffer progressive loss and aggregation of proteotoxins as well (Liang, Wang, Peng, Gan, & Guan, 2010). Moreover, conditional deficiency of Ulk1 in the central nervous system also results in neuronal loss and degeneration, which normally serves as a key kinase triggering the formation of PI3P (Joo, Wang, Frankel, Ge, & Xu, 2016) (Table 2).…”
Section: Pathological Association Between Autophagic Pathways and Alzmentioning
confidence: 99%